FC039: Associations between Maternal Antenatal Systemic Glucocorticoids Usage and Childhood Chronic Kidney Disease. (3rd May 2022) - Hsu, Chien-Ning; Tain, You-Lin
Abstract: BACKGROUND AND AIMS: The effect of antenatal glucocorticoid exposure on offspring health is currently unclear. Therefore, this study examined the association of maternal exposure to systemic glucocorticoids in the past and during pregnancy with the risk of chronic kidney disease (CKD) development in childhood. Methods: A retrospective cohort study of maternal-child dyads was identified from the largest healthcare delivery system in Taiwan between 1 January 2004 and 31 December 2018. Primary analyses were used to compare past and gestational exposures with non-exposure to systemic glucocorticoid considering an inverse probability of treatment weight to adjust the hazard ratio of offspring CKD development in singleton child-matched pairs. Offspring birthweight, sex, gestational weeks stratified analyses and sibling-matched sensitivity analyses were performed to ensure the robustness of the primary study results. RESULTS: In a cohort with 31 927 singleton born children, the cumulative incidence of CKD was 2.23% ( n = 713), with 3.18% ( n = 63) in the gestational glucocorticoid-exposed group, 1.91% ( n = 58) in the past exposed group and 2.2% ( n = 592) in the non-exposed group. Gestational exposure, compared with non-exposure, was significantly associated with a higher risk of childhood CKD (inverse probability therapeutic weighted hazard ratio [wHR], 1.42 [95% confidence interval (95% CI) 1.05–1.92] in Figure. 1 A, but not past exposure (wHR: 0.89, 95% CI 0.67–1.18) (Figure. 1B). In male children, the risk of CKD was significantly higher among gestational-exposed children than among unexposed children (wHR: 1.72, 95% CI 1.21–2.43). The cohort with sibling matched children did not show a significantly increased risk of childhood CKD associated with gestational exposure (wHR: 1.31, 95% CI 0.79–2.18) (Figure. 1A). CONCLUSION: Maternal gestational glucocorticoid treatment was found to be significantly associated with CKD development in children. These findings may support clinicians in performing benefit-risk assessment and in decision-making for systemic glucocorticoid treatment during pregnancy, in clinical settings.